Ayurvedic Management of STXBP1 Encephalopathy with West Syndrome - A Case Report - Roshni Anirudhan; Parvathy Jayan (International Journal of Ayurveda and Pharma Research, 2024)
Developmental delay, intellectual disability, and epilepsy are hallmark features of STXBP1 encephalopathy. This condition is often associated with West syndrome, characterized by intractable epilepsy, developmental regression, and hypsarrhythmia on EEG. Even though timely intervention is crucial, Conventional medical systems lag behind to tackle the developmental regression and to gain control over the intractable epilepsy even with multiple anti epileptic drugs (AEDs). This is a case of a 7-year-old girl with an STXBP1 mutation, clinically diagnosed with West syndrome. She presented to the Kaumarabhritya OPD with significant developmental issues, including inability to sit without support, difficulty rising from a lying position, tremors, poor coordination, truncal ataxia, impaired speech, cognitive deficits, socialization issues, and intractable epilepsy. Ayurvedic management strategy was designed incorporating treatment principles of Apasmara (seizures), Unmada (insanity), Vatavyadhi (Vata disorders), and Sirakampa (head tremors), as an adjunct to ongoing AED regimen. Remarkable improvements were observed in motor, social, and language domains in a period of 4 months. Treatment efficacy was assessed using the Hague seizure severity scale, (improved from 24 to 49) and Gross Motor Function Measure score (increased from 18% to 30%). Receptive language age advanced from 0-1 month to 7-8 months, and expressive language age improved from 0-1 month to 10-12 months. Vineland Social Maturity Scale score improved from 3.5 to 8, and Indian Scale for Assessment of Autism score decreased from 130 to 105. This case report highlights the efficacy of Ayurvedic interventions in curtailing intractable epilepsy, arresting the neuronal regression and triggering the brain growth velocity.